Duplex-specific nuclease-mediated target recycling amplification for fluorescence detection of microRNA. Issue 2 (14th December 2018) - Tan, Lin; Xu, Liu; Liu, Jin-Wen; Tang, Li-Juan; Tang, Hao; Yu, Ruqin
Abstract : Isothermal amplification techniques for nucleic acid detection have drawn increasing interest recently due to the simplicity and low-cost of instruments. Abstract : Isothermal amplification techniques for nucleic acid detection have drawn increasing interest recently due to the simplicity and low-cost of instruments. We have developed a novel duplex-specific nuclease (DSN)-mediated target recycling amplification strategy for microRNA detection. The method utilizes the different adsorption ability of graphene oxide (GO) between single-stranded DNA and double-strand DNA to achieve fluorescence recovery. DSN was employed to mediate target recycling amplification, and desirable sensitivity for miR-21 detection was achieved. The developed method also demonstrated excellent selectivity and applicability for analysis of samples in complex biological media. The application of the developed method for analysis of miR-21 level in three different cell lines demonstrated its potential for real sample analysis.